2004
DOI: 10.1111/j.1365-2745.2004.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant isolation reduces outcross pollen receipt in a partially self‐compatible herb

Abstract: Summary1 Few studies of pollination success in fragmented systems measure stigmatic pollen load, and those that do often find it unrelated to plant or population density, size or isolation. Reduced reproductive output, however, is commonly reported, probably because incompatible pollen is contributing substantially to pollen loads of isolated flowers. 2 We used manipulated floral arrays of a bee-pollinated species ( Dianella revoluta ) to investigate isolation effects on deposition of outcross pollen, while pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 42 publications
(54 reference statements)
3
63
1
Order By: Relevance
“…Duncan et al 2004;Ward and Johnson 2005). Pollinator limitation may not occur when the pollinators are able to Xy long distances.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 98%
“…Duncan et al 2004;Ward and Johnson 2005). Pollinator limitation may not occur when the pollinators are able to Xy long distances.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 98%
“…All of these studies found negative relationships between conspeciWc Xower density (measured either as conspeciWc density or as isolation of target individuals) and individual pollen limitation. Several within-population studies have associated conspeciWc Xower density with other variables that are related to pollen limitation, such as seed/ fruit production (Roll et al 1997;Somanathan and Borges 2004;Pettersson 1997;Spigler and Chang 2008), pollen deposition and/or removal (Johnson et al 2003;Duncan et al 2004), stigma persistence (Wagenius et al 2007), or seed/ fruit production in combination with pollinator visits and/or pollen deposition (Aizen 1997;Waser 1999, 2001;Caruso 1999;Caruso 2002;Kirchner et al 2005).…”
Section: Conspeciwc Density and Pollen Limitationmentioning
confidence: 98%
“…isolation of the plant population), through lowered pollinator density (caused by isolation of pollinator habitat) and through changes in pollinator movement [12]. Isolated plant populations can show lower pollination success independent of pollinator visitation because of a lack of compatible donor plants [18]. In turn, the absence of pollinators can decrease pollination success even in situations where the availability of donor plants is high [15].…”
Section: Introductionmentioning
confidence: 99%